2015
DOI: 10.1111/dme.12774
|View full text |Cite
|
Sign up to set email alerts
|

Does kindness matter? Self‐compassion buffers the negative impact of diabetes‐distress on HbA1c

Abstract: In addition to further demonstrating the link between distress and metabolic outcomes, these findings suggest that self-compassion might buffer patients from the negative metabolic consequences of diabetes-distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 29 publications
4
49
0
Order By: Relevance
“…Some studies suggest that DD does not discriminate by diabetes type (3,4), but it cannot be presumed that emotional problems are similarly experienced, and have the same consequences in Type 1 and 2 diabetes. Indeed, the most commonly reported emotional problems in Type 1 diabetes relate to hypoglycaemia and complications; worry about the future and complications, feeling burnt out/overwhelmed, and worrying about low blood sugar reactions (5-7), whereas in Type 2 diabetes emotional distress relates more to goal setting and food restrictions (7).…”
Section: Manifestation Of Diabetes Distress In Type 1 and Type 2 Diabmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies suggest that DD does not discriminate by diabetes type (3,4), but it cannot be presumed that emotional problems are similarly experienced, and have the same consequences in Type 1 and 2 diabetes. Indeed, the most commonly reported emotional problems in Type 1 diabetes relate to hypoglycaemia and complications; worry about the future and complications, feeling burnt out/overwhelmed, and worrying about low blood sugar reactions (5-7), whereas in Type 2 diabetes emotional distress relates more to goal setting and food restrictions (7).…”
Section: Manifestation Of Diabetes Distress In Type 1 and Type 2 Diabmentioning
confidence: 99%
“…The DDS and DDS-T1 are comprised of empirically established sub-scales such as the DDS emotional burden and regimen distress sub-scales (20,27) and have been employed in research studies (28). Short forms and screeners such as the DDS2 and PAID-5 are also available (3,(29)(30)(31)). …”
Section: Measurement Of Diabetes Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to predicting a higher negative affect, the emotional burden of distress about managing one's diabetes may be a qualitatively different experience from depression per se (3,4). Although both distress and depression are linked to poor glycemic control, evidence suggests that distress rather than depression may be a better predictor of metabolic outcomes (3,5). Of note, given the scale and impact of mood disturbance among patients with diabetes, evidence for psychological interventions that successfully treat depression and distress and, ideally, concurrently improve metabolic outcomes is limited.…”
mentioning
confidence: 99%
“…Evidence in both healthy and patient populations (12) has linked greater self-kindness with better mood, and a meta-analysis of nearly 80 studies has shown a large effect size (r = 0.47) in the relationship between self-compassion and well-being (13). Although evidence from diabetes is scanty, one study found that self-compassion predicted less diabetes-specific distress and buffered the link between diabetes distress and poor metabolic outcomes (5).…”
mentioning
confidence: 99%